The effect of environmental stimuli on the implementation of the agility policy in logistics villages of Tehran province - Mahdi Zoghi; Mohammad Reza Rabiee Mandejin; alireza Amirkabiri (ارزش آفرینی در مدیریت کسب و کار, 2024)
Abstract The purpose of this research is to investigate the impact of environmental stimuli on the implementation of the agility policy in logistics villages of Tehran province. The current research is applicable-developmental in terms of purpose. The statistical population of the research includes managing directors and members of the board of directors, deputies, managers and heads and supervisors of different departments of logistics villages in Tehran province, whose number is 99 and the sampling method is total number. The information collecting tool was the questionnaire of environmental stimuli made by the researcher, taken from the qualitative section. The reliability of the research was checked and confirmed using Cronbach's alpha criterion in SPSS software. SPSS software was also used for data analysis, and PLS software was used for structural equation modeling. The findings of the research showed that the acceptance percentage of the language term "very high pressure and impact" is confirmed for the category of the impact of environmental stimuli on the implementation of the agility policy of the administrative system of logistics villages in Tehran province, and also the model has a good fit. Extended Abstract Introduction One of the most important policies included in the policies of the administrative system announced by the Supreme Leader is the issue of making administrative structures agile and flexible (paragraphs 10 and 11 of the mentioned document) (Office of Preservation and Publishing of Her Holiness's Works, 2009). And the reason for this importance and emphasis on it is the scientific and research propositions of great scientists and researchers such as Goldman (1995) and SE Lootah et al, (2020) that tie the issue of agility of administrative systems to their survival and organizational life. Evaluation is part of the most important requirements for the perfection of public policies, including the agility of administrative systems, which guarantees their thought-oriented, accurate implementation, and continuous improvement (Vaezi & MOhammadi, 2017). According to many experts, evaluation of implementation is a legal requirement, but in principle, evaluation is a way for effectiveness, policy improvement, policy development, service delivery, ensuring the fulfillment of needs, and using existing potentials. The main core of the new policy is the evaluation that can lead to the effectiveness and efficiency of the service (Equality and Human Rights Commission (EHRC)); this proposition is obviously imaginable and generalized for evaluation of agility policy in logistic villages. Determining suitable areas for the construction of logistics villages and determining its functions in the "Document for the preparation of logistics centers of the country" as an upstream document in 2017 was approved by the Ministry of Roads and Urban Development of IRI., and "Public Warehouses and Customs Services Company of Iran" to as the only example of logistics centers in the country, whose nationalization was approved by the Revolutionary Council of IRI. in the meeting dated 2/20/1359, will be studied as the target community. Logistics centers in different countries not only act as connecting points of different types of transportation, but have appeared as links connecting trade and transportation (Uyanik et al, 2018), which shows the importance of these institutions in the formation and development of logistics in the country. Therefore, the researcher is trying to answer the question: what is the effect of environmental stimuli on the implementation of the agility policy in logistics villages of Tehran province? Theoretical Framework Policy The measures necessary for the effectiveness or execution of the selected policies are concentrated, which is called policy implementation. Enforcement of public policies refers to the enforcement of a specific policy decision in accordance with the law, the court, or the directives of any administrator. In the process of managing policies, they are often developed or added in their details. One of the main stages of policy making is its implementation stage. Establishing a logical and appropriate communication between policy makers and implementers is considered one way to develop countries and it will cause the opinions of employees at the level of organizations and the views of people at the level of society to be somehow involved in policy making and drafting of laws. Paying attention to implementation in the policy-making process accelerates the realization of the goals of the system and leads to the realization of bureaucracy in society (Parsanasab et al, 2022). Organizational Agility Organizational agility can be considered an organizational competency and ability to effectively engage with the ecosystem and help organizations to keep up with technological, economic, social and cultural challenges in a changing environment (Dupont, 2019). Research background Rahimi et al, (2023) discussed the effect of using knowledge management on organizational agility with the mediating role of innovation in defense project-oriented organizations. The findings of this research showed that the application of knowledge management had a direct, positive and significant effect on the agility of defense project-oriented organizations with a coefficient of 0.498, and it can also increase organizational agility through organizational innovation with an indirect effect and a coefficient of 0.363. Therefore, defense project-oriented organizations should focus more on the effective implementation of knowledge management, so that through strengthening innovation and improving the level of organizational agility, they can respond to the rapid changes in the defense environment and create a suitable level of defense deterrence. Parsanasab et al, (2022) examined the presentation of a model for the acceptance of public policies in the field of personnel by the target community. The relevant results showed that the value of the GOF index for the numerical model is equal to 0.495, which is a strong index and shows the overall high quality of the model. Based on this index and other indicators of the model, it was proved that the 22 identified criteria can, in general and in the form of a model, well measure the acceptance of the public policy, and the effects of each of the criteria present a suitable predictability. The impact of the identified variables in the model showed that all the identified factors have a significant effect in explaining the acceptance of the policies. The factor of interference and policy dependence, the methods of implementing the interference policy and the culture of the target society, and the environment of the target society have the greatest effect in explaining the acceptance of policies, and organization has the least effect.